Politik Hukum Mahkamah Konstitusi dalam Membatalkan Konsep Empat Pilar sebagai Upaya Mendudukkan Pancasila Sebagai Dasar Negara - Udiyo Basuki (UIN Sunan Kalijaga Yogyakarta, 2015)
This paper is the result of research that has been overshadowed by the studyauthors theoretical and empirical, that Pancasila is the basis of the state and a source oflaw as stated in the Preamble to the Constitution of the Republic of Indonesia Year1945 fourth paragraph. In the system of legislation, Pancasila is the basic norm(staatsfundamental), successive later verfassungnorm 1945, grundgezetznorm or MPRdecrees, as well as gezetznorm or the Act. But in reality, the Pancasila likened hisposition and aligned with the 1945 Constitution, the Unitary Republic of Indonesia,Unity which was then called the